The investigation and analysis of nutritional iron deficiency anaemia in Kazakh children - Wei, Yu; Wang, Jianghong; Wang, Feng; Wang, Xu; Cheng, Xiufang (Frontiers in Pediatrics, 2026)
ObjectiveThis study aimed to investigate nutritional iron deficiency anaemia (IDA) in Kazakh children.MethodIn this cross-sectional study, a total of 197 children aged 3–14 years were randomly selected from three townships in Barkol County, and the basic information and diet of the sample children were collected and analysed.ResultsThe overall prevalence of IDA was 15.7%, which is considerably higher than the national average for children in China. Kazakh children had a significantly higher prevalence of anaemia than their Han counterparts (p = 0.040). To ensure statistical stability given the sample size, a parsimonious multivariate logistic regression model was employed. This model identified lower intake of meat [adjusted odds ratio (aOR) = 0.92], lower intake of aquatic products (aOR = 0.35), and failure to take iron supplements (aOR = 5.10) as independent risk factors for IDA.ConclusionsThe findings indicate a substantial burden of IDA among Kazakh children in this region, highlighting a significant ethnic disparity. The primary modifiable risk factors are dietary, centring on insufficient consumption of bioavailable iron from animal sources and aquatic products, coupled with a lack of iron supplementation. The counterintuitive association between soybean/nut intake and IDA risk warrants further investigation. These results underscore the urgent need for targeted nutritional interventions and health education programmes focused on improving dietary iron quality and supplementation practices in this population.